1987
DOI: 10.1111/j.1365-2494.1987.tb02125.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of weather and nutrition on the yield of hay from Palace Leas meadow hay plots, at Cockle Park Experimental Farm, over the period from 1897 to 1980

Abstract: The yield of hay on the Palace Leas meadow hay plots has increased significantly with time on the higher yielding plots but has remained constant on the iower yielding plots. Yield on the higher yielding plots shows a relatively low fluctuation from year to year, and yields of plots treated with farmyard manure show high intercorrelations with each other, but lower correlations with the other plots. Yield is influenced by weather, but even the most successful climatic parametermaximum soil moisture deficit-onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 6 publications
2
7
0
Order By: Relevance
“…This negative correlation between plant-available P content in soil and biomass production is consistent with the Palace Leas Meadow Hay Plot Experiment (Coleman et al 1987;Shiel and Batten 1988), in which various fertilizer treatments created plant communities of different plant species composition. In the control plot, the content of plant-available P was higher but mean dry matter biomass production was lower than in N-fertilized plots.…”
Section: Discussionsupporting
confidence: 80%
“…This negative correlation between plant-available P content in soil and biomass production is consistent with the Palace Leas Meadow Hay Plot Experiment (Coleman et al 1987;Shiel and Batten 1988), in which various fertilizer treatments created plant communities of different plant species composition. In the control plot, the content of plant-available P was higher but mean dry matter biomass production was lower than in N-fertilized plots.…”
Section: Discussionsupporting
confidence: 80%
“…Over the earlier period, there was a non-significant decline in total yield on plot 16d, in contrast to an increase on plot 14d which is just significant, assuming that there is no autocorrelation. Coleman et al (1987) likewise found that the yields of fertilized hay in the Palace Leas Experiment in Northumberland were autocorrelated, whereas yields on the unfertilized plots were not.…”
Section: Results Of Statistical Analysesmentioning
confidence: 87%
“…More, or more sophisticated, climatic variables might explain more of the variance in composition. However, we have found that potential soil moisture deficit, which is usually a good correlate of grass growth (e.g., Coleman et al 1989), performs little better than rainfall as an explanatory variable in the PGE (M. Dodd, unpublished data). An alternative explanation is that rainfall controls competitive interactions among the grasses, legumes, and other species, and that the ratio of these components is thus affected by two mechanisms: the first is due to the preferential effect of rainfall on grass growth, and the second is due to the competitive suppression of legumes and other species when grass growth increases, which the success of model 12 (Table 3) suggests probably operates with a time lag of a year.…”
Section: Response Of Community Compositionmentioning
confidence: 99%